2008
DOI: 10.1016/j.neuropharm.2008.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter dosage modulates long-term decision-making in rat and human

Abstract: a b s t r a c tDecision-making plays an important role in everyday life and is often disturbed in psychiatric conditions affected by the common human serotonin transporter promoter length polymorphism (5-HTTLPR). This raises the hypothesis that decision-making is modulated by the serotonergic system, but currently it is unclear how the 5-HTTLPR affects central serotonergic functioning. We tested healthy human volunteers genotyped for the 5-HTTLPR in the Iowa Gambling Task (IGT), which is one of the most freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 34 publications
9
79
1
Order By: Relevance
“…Increased choice of the disadvantageous options in the IGT has also been observed in healthy volunteers carrying the short allele of the serotonin transporter-linked polymorphic region (5-HTTLPR (s) ;Homberg et al, 2008). Although it is currently unclear what inheritance of 5-HTTLPR (s) means for the functioning of the 5-HT system (Lesch et al, 1996;van Dyck et al, 2004), rats which are homo-or heterozygous SERT knockouts, and therefore have constitutively higher levels of extracellular 5-HT, were better at performing a rodent gambling task in which loss was signaled by the addition of quinine to the reward pellets (Homberg et al, 2008). On the basis of these data, decreasing 5-HT efflux would be expected to increase risky choice.…”
Section: Serotonergic Modulation Of Rgt Performancementioning
confidence: 99%
“…Increased choice of the disadvantageous options in the IGT has also been observed in healthy volunteers carrying the short allele of the serotonin transporter-linked polymorphic region (5-HTTLPR (s) ;Homberg et al, 2008). Although it is currently unclear what inheritance of 5-HTTLPR (s) means for the functioning of the 5-HT system (Lesch et al, 1996;van Dyck et al, 2004), rats which are homo-or heterozygous SERT knockouts, and therefore have constitutively higher levels of extracellular 5-HT, were better at performing a rodent gambling task in which loss was signaled by the addition of quinine to the reward pellets (Homberg et al, 2008). On the basis of these data, decreasing 5-HT efflux would be expected to increase risky choice.…”
Section: Serotonergic Modulation Of Rgt Performancementioning
confidence: 99%
“…Thus, carriers of the ss allele of the 5-HTTPLR gene have shown enhanced attention toward probability cues during the performance of a risky choice task compared with carriers of the ll allele (Roiser et al, 2006), fewer risky choices in a financial investment task (Kuhnen and Chiao, 2009), and smaller impairments in probabilistic reversal tasks following tryptophan depletion (Finger et al, 2007), especially under aversive reinforcement conditions (Blair et al, 2008). Notably, female ss carriers have also shown poorer decisions under conditions of decision ambiguity (Stoltenberg and Vandever, 2010), poor performance of the Iowa gambling game compared with carriers of the ll allele (Homberg et al, 2008), and especially in OCD samples (da Rocha et al, 2008).…”
Section: Serotonin and Decision Makingmentioning
confidence: 99%
“…We genotyped a further three serotonergic functional polymorphisms (5HTTLPR in serotonin transporter, rs6295 in 5HTR1A receptor, and rs1800532 in TPH1 genes) but could not demonstrate significant main effects of these polymorphisms or interaction with the TPH2 htSNPs on risk taking. However, we could not exclude that these genes modulate other aspects of decision making that were not measured by our task, such as punishment-or feedback-related processing, as previous studies reported (Jollant et al, 2007;Must et al, 2007;Blair et al, 2008;Homberg et al, 2008). Accumulating evidence suggest that the more common allele/haplotype variants in the TPH2 gene are associated with lower cerebrospinal fluid 5-hydroxyindoleacetic acid concentrations (Zhou et al, 2005) and with decreased TPH2 mRNA expression Haghighi et al, 2008;Lim et al, 2007).…”
Section: Discussionmentioning
confidence: 88%
“…It has been reported that possession of the less active S allele of the 5-HT transporter 5HTTLPR polymorphism (SLC6A4 gene short/S-long/L promoter variant) increased sensitivity to the probability of winning in a 'risky-choice task' (Roiser et al, 2006) and promoted disadvantageous choices in the Iowa Gambling Task (IGT) probably due to lack of persistence (Must et al, 2007;Homberg et al, 2008) or to slower learning of advantageous decision making (Jollant et al, 2007). It has also been suggested that 5HTTLPR variations modulate sensitivity to punishment rather than reward, as the LL homozygous individuals are less sensitive to punishment-related information (Blair et al, 2008;Roiser et al, 2009).…”
Section: Introductionmentioning
confidence: 99%